PDL1 inhibitors may be associated with a lower risk of allograft rejection than PD1 and CTLA4 inhibitors: analysis of the WHO pharmacovigilance database - Gérard, Alexandre O.; Merino, Diane; Benzaquen, Jonathan; Destere, Alexandre; Borchiellini, Delphine; Gosset, Clément; Rocher, Fanny; Andreani, Marine; Marquette, Charles-Hugo; Montaudié, Henri; Drici, Milou-Daniel; Sicard, Antoine (Frontiers in Immunology, 2025)
BackgroundTransplant recipients face increased cancer mortality due to immunosuppressive treatments. Immune checkpoint inhibitors (ICI) have improved survival rates, but data on the use of these agents in transplant recipients is scarce. ICI may trigger allograft rejection, but the absolute risk of AR between the different ICI classes remains to be defined.MethodsVigiBase® (WHO’s pharmacovigilance database) was queried for reports of AR involving CTLA4, PD1, or PDL1 inhibitors. Disproportionality analysis compares the proportion of reports with a specific adverse drug reaction (ADR) and a given drug to the proportion of reports with the same ADR and other drugs. A lower 95% confidence interval for the Information Component (IC) >0 suggests a signal. The comparative Reporting Odds Ratios (ROR) for AR, between PD1 and PDL1 inhibitors, was calculated.ResultsWe gathered 159 AR involving an ICI, especially nivolumab (73, 45.9%), mostly affecting kidneys (87, 54.7%). Median time to onset: 28 days. Fatal outcome: 36 reports (22.6%). ICI were significantly associated with AR: IC=1.7 [1.4;1.9]. Specifically, PD1 inhibitors yielded an IC of 2.0 [1.7;2.2] (152 reports observed compared to 38 expected). By contrast, the IC of PDL1 inhibitors was negative: -2.6 [-6.4;-1.0] (1 observed, 9 expected). The comparative ROR of PD1 compared to PDL1 inhibitors was 33.7 [4.7;240.9] (p=0.0005).ConclusionsWe confirm the association between ICI treatment and AR. Notably, PDL1 inhibitors showed surprisingly low AR reports compared to CTLA4 and PD1 inhibitors. Further prospective studies are warranted to confirm whether PDL1 inhibitors indeed reduce AR risk compared to other ICI.